The EFL Students’ Perception Toward the Use of Wattpad To Help in Reading Comprehension - Agis Andriani; Yuyus Saputra; Riska Azizah Hendriani (Institut Agama Islam Negeri Palopo, 2023)
This study aims to explore the EFL students’ Perception on use of the Wattpad application in helping reading comprehension. The research method used is a qualitative case study. The participants were three English Education students at a university in West Java, Indonesia. The data collection was carried out using semi-structured interviews. Then, the data analysis used the thematic analysis framework from Braun and Clarke (2006). The results of the study found two themes, namely (1) Wattpad Facilitates users for Reading Easily and (2) Achievement of Reading Comprehension Levels. The contribution of this research is to provide readers with empirical insight into the advantages of the Wattpad application to assist in reading comprehension